2002
DOI: 10.1002/j.1551-8833.2002.tb09458.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Water Quality deterioration in Finished Water Storage Facilities

Abstract: Finished water storage facilities play a key role in maintaining the quality of drinking water ultimately received by consumers. Without proper design, operation, and maintenance of these facilities, stored water may easily become stagnant and subject to loss of chlorine residual, as well as bacterial regrowth, contaminant entry, and a host of other water quality problems. Given that finished water storage facilities are part of the country's problem with aging infrastructure and that distribution system water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Water entered Compartment A at a constant flow rate, Q in (t), and an inlet concentration of C in (t). Then, it flowed into Compartment B at the same rate as before, with a new fluoride concentration, (8), formed by mixing in Compartment A. Figure 3b shows a graphical representation.…”
Section: Configuration 1: Initial Level Of Water and Inlet Point Of Compartment Amentioning
confidence: 99%
See 2 more Smart Citations
“…Water entered Compartment A at a constant flow rate, Q in (t), and an inlet concentration of C in (t). Then, it flowed into Compartment B at the same rate as before, with a new fluoride concentration, (8), formed by mixing in Compartment A. Figure 3b shows a graphical representation.…”
Section: Configuration 1: Initial Level Of Water and Inlet Point Of Compartment Amentioning
confidence: 99%
“…An experiment conducted by [7] showed that ammonia-oxidizing bacteria (AOB) concentrations in the surface layer (0.3 m below the surface) were 10-20 times greater than concentrations 5 m below the surface. The deterioration of water quality in Philadelphia's ground-level storage tanks was investigated by [8]. During the summer, reservoirs were discovered to have thermal, chemical, and microbiological stratification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, more and more emphasis had been placed on distribution systems and storage facilities, which play a critical role in drinking water qualities. As a matter of fact, more and more research studies (Haas et al 2002;Martel et al 2002) considered these two factors as important barriers within water supply systems, along with the traditional multiple treatment barriers. In the past decade, emphasis had been placed on distribution system related issues, and the research results showed that the material and size of pipelines, chemical characteristics of bulk water, hydraulic conditions, distance from water facilities, and configuration of networks all influence water qualities throughout the distribution systems (Baribeau et al 2001).…”
Section: Introductionmentioning
confidence: 98%
“…Many efforts have been made to reduce water age in order to minimise water quality degradation in drinking water networks, whether by rerouting flow paths, through valve operation [13], by increasing nodal outflows at critical dead-end nodes (through the opening of a blow-off at the hydrant site) [14], or by increasing storage tanks' daily turnover rates to reduce water ageing in storage facilities [15]. In water quality optimisation studies, the objective is often to minimise water age at the consumption nodes without setting water age goals [10,11].…”
Section: Introductionmentioning
confidence: 99%